Pharmacokinetics and tolerability of prefilled syringe and auto-injector presentations of MSB11456: results of a randomized, single-dose study in healthy adults. (3rd April 2023) - Tomaszewska-Kiecana, Monika; Dryja, Anna; Ullmann, Martin; Petit-Frere, Corinne; Illes, Andras; Dagres, Christos; Monnet, Joëlle
ABSTRACT: Background: Tocilizumab is a monoclonal immunoglobulin G interleukin-6 receptor antagonist. MSB11456 is a proposed tocilizumab biosimilar. Objective: To determine the pharmacokinetic equivalence of a single subcutaneous injection of MSB11456, when delivered via autoinjector (AI) and prefilled syringe (PFS), in healthy adult subjects. Research design and methods: In this randomized, open-label, single fixed-dose, crossover study, 91 subjects received subcutaneous administration of tocilizumab 162 mg via AI and PFS presentations. The primary endpoint pharmacokinetic parameters were analyzed using analysis of variance. Safety data were summarized descriptively. Results: There were no differences in pharmacokinetic parameters between presentations, and safety parameters were comparable. The 90% confidence intervals for the geometric least squares mean ratios of all primary pharmacokinetic parameters were contained within the predefined 80.00% to 125.00% bioequivalence limits, indicating pharmacokinetic equivalence between the AI and PFS. Conclusions: MSB11456 administration via AI was bioequivalent to administration via PFS. MSB11456 can be administered by AI or PFS, increasing the available range of self-injection devices. Trial registration: The trial is registered at EudraCT, number 2020–003419-86. Plain Language Summary: Tocilizumab is a biologic drug that is used to treat autoimmune diseases, including rheumatoid arthritis. MSB11456 has been shown to be equivalent to the US-licensed and EU-approved tocilizumab when administered by subcutaneous injection. There are different devices available to administer subcutaneous injections, and depending on the device, the patient's experience can be enhanced, convenience and compliance increased, and cost-effectiveness ensured for patients taking this medicine. This randomized, single fixed-dose, crossover study tested the pharmacokinetic similarity of MSB11456 when given subcutaneously via an auto-injector device versus a pre-filled syringe device in 100 healthy subjects. A total of 91 healthy volunteers received MSB11456 via both auto-injector and pre-filled syringe using a crossover design. Blood was collected before the first dose and at regular intervals during the study to determine the pharmacokinetics of tocilizumab and ensure safety. This study found that the pharmacokinetics of tocilizumab following administration using the autoinjector and the prefilled syringe were equivalent, and the safety profiles were similar. These findings indicate that the auto-injector can be considered another option that can be used to subcutaneously inject MSB11456.